Regulation of securities markets : an examination of the effects of increased competition - Stoll, Hans R. (New York, N.Y. : New York University, Graduate School of Business Administration, Salomon Brothers Center for the Study of Financial Institutions, 1979)
The study is concerned only with the brokerage function of the securities market.
Cover title.
Includes bibliographical references: p. 81-83.
oif 11/07/2018
Loans
Keywords: Brokers---Fees; Securities market; United States